Efek Investasi Terhadap Pertumbuhan Ekonomi di Pulau Jawa dan Pulau Sulawesi - Muh Jamil (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
This research aimed to analyze Efect Of Investment to economic growth in Java island and Sulawesi island in 2006-2013. The research used the secondary data, time series and cross section of the eight provinces, namely Jakarta, West Java, Central Java, East Java, North Sulawesi, Central Sulawesi, South Sulawesi and Southeast Sulawesi. The data used comprised the investment index and economic growth index. The data were then Analyzed using Structural Equation Model (SEM) processed using Amos and SPSS econometric software. The results showed that the effect of investment on positive economic growth was significant on Java and positively insignificant on Sulawesi Island. That means that each increase in investment by one percent increases economic growth by 0.479 percent on Java and on Sulawesi Island investment has no effect on economic growth. The investment spread in Java is more stable from year to year and from region to region. Different things on the island of Sulawesi, investment is not stable, sometimes very high and sometimes also very low in other years